Antioxidant Effects of Walnut (Juglans regia L.) Kernel and Walnut Septum Extract in a D-Galactose-Induced Aging Model and in Naturally Aged Rats - Marius Emil Rusu; Carmen Georgiu; Anca Pop; Andrei Mocan; Bela Kiss; Oliviu Vostinaru; Ionel Fizesan; Maria-Georgia Stefan; Ana-Maria Gheldiu; Letitia Mates; Rebeca Moldovan; Dana Maria Muntean; et al. (MDPI AG, 2020)
Antioxidant dietary intervention is considered a potential strategy in delaying age-related dysfunctions. In this study of 56 days, we assessed the antioxidant effects of walnut kernel (WK) and walnut septum extract (WSE) in a D-galactose (D-gal)-induced aging model and in a naturally aged rat model. Young Wistar rats, treated with D-gal (1200 mg/week), and old rats received daily WK or WSE added to the feed. After 8 weeks, blood, liver, and brain samples were collected and hematological, biochemical, oxidative stress biomarkers, histological, and immunohistochemical analyses were performed. Moreover, acetylcholinesterase activity was investigated in brain homogenates. The outcomes demonstrated significant improvement in cellular antioxidant activity and/or decrease of reactive oxygen species, advanced glycation end products, nitric oxide, malondialdehyde, or increase of glutathione after WK or WSE intake in both models. Additionally, WSE showed hypoglycemic effect, and both WK and WSE lowered acetylcholinesterase activity. Both diets could protect neurons against the induced senescence and could reverse the pathological conditions in the physiological aged brain. Thus, dietary supplementation with WK or WSE can maintain the liver and brain health and reduce the risk of age-related diseases, as well as delaying the onset of aging processes.